Gender, self-efficacy and performance in a mathematics test: The moderating role of the educational center - Zamora-Araya, José Andrey (2022)
[Objective] The purpose of the present study was to analyze the relationship between students’ mathematical self-efficacy and performance in the national high school graduation mathematics test, taking into account other relevant psychosocial predictors and the moderating effects of sex and educational center. [Methodology] The design of the study was observational and cross-sectional, with the participation of 487 eleventh-grade students from public secondary schools in the Greater Metropolitan Area of Costa Rica. Several instruments were applied for measuring hostile and benevolent sexism, perceptions of gender equality in mathematical abilities, mathematical self-efficacy and reasoning abilities. [Results] The results of the multilevel Bayesian random effects analysis confirmed that scores were higher for men than for women in measurements of self-efficacy, where the sex of the student body was a moderator in the relationship of mathematical self-efficacy and test scores. In addition, it was found that, depending on the sex of subjects, the association between self-efficacy and performance was also moderated by the educational center. [Conclusions] Among the conclusions, it is especially noteworthy that if the moderating effect of the educational center between self-efficacy and performance differs by sex, this implies that actions aimed at promoting self-efficacy will not have the same result in men and women, showing the need to develop differentiated interventions.